Ultrassonografia doppler para parâmetros fluxométricos da artéria uterina média de cadelas em estágios fisiológicos e patológico (Piometra) - LACERDA, Maria Albeline Silva de (2015)
The hemodynamic of uterine arteries and the adequate blood supply are important to the uterine physiology. The aim of this study was to determine patterns of flowmetry of uterine arteries using Doppler ultrasonography, in physiologic conditions (estrous cycle) and pathologic (pyometra). The animals (n=56) were distributed in heterogenic samples of each phase of estrous cycle (proestrous – n=7, estrous – n=5, dietrous – n= 19 and anestrous – n=13) or pyometra (n=12). All studied animals were submitted to ultrasound mode B exam, and media uterine artery was identified using Doppler tools. The pulsativity (IP), resistivity (IR) and systole/diastole (S/D) indexes and diastolic end (ED), systolic pick (PS), TAMAX, and heart rhythm (HR) were automatically determined by the ultrasound machine. The results showed that there is no significant difference between analyzed parameters and estrous cycle phases. However, comparing healthy animals in diestrus with pyometra, higher averages (P <0.05) of IP (8.54 ± 5.92) and IR (1.00 ± 0.11) was observed in the healthy compared to those with pyometra (PI = 4.49 ± 2.51 and 0.89 ± IR = 0.13). It was also observed higher mean TAMAX in pyometra (6.09 ± 15.09 cm/s) compared to healthy animals (2.72 ± 1.94 cm/s). With respect to the PS, a tendency (P = 0.07) of higher mean value was observed in pyometra (29.8 ± 15.35 cm/s) compared to healthy animals in diestrus phase (23.08 ± 8.61 cm/s). The other parameters showed no difference between groups. It was concluded that the phases of the estrous cycle do not interfere with hemodynamic parameters. Furthermore, the uterine artery blood flow has increased speed and decreased vascular resistance associated with pyometra.